Spontaneous Massive Vulvar Edema in Pregnancy: A Case Report - Olivier Mulisya; Mbusa Mastaki; Tambavira Gertrude; Kyakimwa Tasi; Jeff K. Mathe (Hindawi Limited, 2018)
Spontaneous massive vulvar edema in pregnancy is unusual and a cause for concern. This condition should be taken seriously since it might be caused by some conditions such as preeclampsia, diabetes, vulvovaginitis, severe anemia, and neoplasms. We report a case of massive vulvar edema in a 15-year-old primigravida following tocolysis therapy at 33 weeks of gestation. Other causes of vulvar edema were excluded. The vulvar edema appeared spontaneously after tocolysis and rapidly increased in size, associated with severe vulvar pains. The vulvar edema resolved progressively with antibiotics, corticoids, and analgesics. The patient delivered by spontaneous vaginal delivery a term live newborn with an unremarkable postpartum period. The aim of this report is to alert clinicians that conservative attempts could be considered for vulvar edema complicating tocolysis.